2019
DOI: 10.5964/jspp.v7i1.1107
|View full text |Cite
|
Sign up to set email alerts
|

The past as a means of persuasion: Visual political rhetoric in Finnish dairy product advertising

Abstract: This study investigates the role of advertising and visual rhetoric in political persuasion. Analysis of Finnish dairy product video advertisements from 2010–2016 focuses on those that exploit time as the main reference framework. A better understanding of how advertising is used as a tool of political persuasion is sought by exploring the following questions: How are advertisements used in political communication? How is time used as a means of persuasion in advertising? What role do visual rhetoric and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
(45 reference statements)
0
13
0
1
Order By: Relevance
“…On the third level of analysis, we combined the analyses of content and form, analyzing the images in their immediate and broader argumentative context. Following the example of Hakoköngäs and Sakki (2019), we argue that interpretation of these elements together is a way to interpret the rhetorical functions conveyed by the material. In the analysis of persuasion, our focus was on the rhetorical organization of the memes, that is, what the rhetorical forms were, such as, factuality- and credibility-enhancing strategies (e.g., Potter, 1996), and strategies of persuasion, such as, out-group derogation or enhancement of in-group identity (e.g., Pettersson & Sakki, 2017), and what the memes made use of and for what purposes.…”
Section: Methodsmentioning
confidence: 99%
“…On the third level of analysis, we combined the analyses of content and form, analyzing the images in their immediate and broader argumentative context. Following the example of Hakoköngäs and Sakki (2019), we argue that interpretation of these elements together is a way to interpret the rhetorical functions conveyed by the material. In the analysis of persuasion, our focus was on the rhetorical organization of the memes, that is, what the rhetorical forms were, such as, factuality- and credibility-enhancing strategies (e.g., Potter, 1996), and strategies of persuasion, such as, out-group derogation or enhancement of in-group identity (e.g., Pettersson & Sakki, 2017), and what the memes made use of and for what purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Such temporal narratives and historical references are valuable in political argumentation, because they concern issues like social identity, tradition, and a sense of continuity (e.g. Hakoköngäs & Sakki, 2019; Levinger & Franklin Lytle, 2001; Sani et al ., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The present study understands multimodality as meaning construc tion contributed by moving images, verbal and textual narration and music and sound (Kress, 2010). de Rosa (2014) and more recently, Hakoköngäs and Sakki (2019) and Martikainen (2019) have suggested that the social representations theory (SRT) is well suited to answer these questions as it gives importance to the iconic dimension of knowledge formation. More broadly, SRT focuses on how ideas, values and beliefs around topical phenomena are negotiated and communicated in society (Moscovici, 1961(Moscovici, /2008(Moscovici, , 1984.…”
Section: What Do These Findings Mean?mentioning
confidence: 99%
“…These qualities are exploited by advertisers to appeal to their audiences. Producers of social justice campaigns may seek to elicit donations and also change social values, ideas and practices, thus uniting rhetoric and social representations as images in a way that can be used persuasively to trigger the formation of new representations (Hakoköngäs & Sakki, 2019;Martikainen, 2019). Simultaneously, images are products of existing social representations held by those creating and disseminating them (de Rosa & Farr, 2001).…”
Section: Multimodal Mediums Of Social Representationsmentioning
confidence: 99%
See 1 more Smart Citation